Transitivity pairs in Baltic: between Finnic and Slavic - Nau, Nicole; Pakerys, Jurgis (Lingua Posnaniensis, 2016)
In this paper we examine transitivity pairs in the two modern Baltic languages Lithuanian and Latvian and compare them to neighbouring Finnic (Finnish, Estonian) and Slavic (Russian, Polish) languages. In Slavic the main strategy is to derive the intransitive (noncausal) verb from the transitive (causal) verb, while in Finnic we find a high number of derived causatives. Baltic uses both techniques, and in addition, there is a higher number of pairs where either both verbs are marked, or two etymologically related verbs are underived from a synchronic point of view. Differences and similarities across the six languages are investigated, using a list of 20 notions divided into five groups. Special attention is paid to animacy and to the distinction between inchoative and durative noncausal verbs.